International Society of Blood Transfusion Working Party on red cell immunogenetics and blood group terminology: Cancun report (2012). Issue 1 (27th December 2013) - Storry, J. R.; Castilho, L.; Daniels, G.; Flegel, W. A.; Garratty, G.; de Haas, M.; Hyland, C.; Lomas‐Francis, C.; Moulds, J. M.; Nogues, N.; Olsson, M. L.; Poole, J.; et al.
<x xml:space="preserve">Abstract</x> The International Society of Blood Transfusion Working Party on red cell immunogenetics and blood group terminology convened during the International congress in Cancun, July 2012. This report details the newly identified antigens in existing blood group systems and presents three new blood group systems.